Distinct activities of Vδ1+ T‐cells upon different cytomegalovirus reactivation status after haematopoietic transplantation. Issue 3 (31st July 2022) - Liu, Ruoyang; Wu, Ning; Gao, Haitao; Liang, Shuang; Yue, Keli; Dong, Tianhui; Dong, Xinyu; Xu, Lan‐Ping; Wang, Yu; Zhang, Xiao‐Hui; Liu, Jiangying; Huang, Xiao‐Jun
Abstract: Cytomegalovirus (CMV) reactivation is the most frequent viral infectious complication correlating to non‐relapse mortality after allogeneic haematopoietic cell transplantation (alloHCT). The intrinsic anti‐CMV immunity has not been completely elucidated. γδ T‐cells have drawn increasing attentions due to their distinct biological features and potential ability against viral infections. Previous studies reported a general association of γδ T‐cells or Vδ2‐negative γδ T‐cells with CMV reactivation. Whereas researches for the direct responses and specific functions of γδ T subsets remain limited, especially in the scenario of alloHCT. Herein, we initially demonstrated that Vδ1 + T‐cells directly and independently recognized cell‐free CMV and CMV‐infected target cells, and inhibited CMV replication in vitro. The anti‐CMV effect of Vδ1 + T‐cells was partially through TCRγδ, TLR2 and NKG2D receptor pathways. Further investigation about the anti‐CMV characteristics of Vδ1 + T‐cells was performed in a clinical cohort with different CMV reactivation status after alloHCT. We found that occasional CMV reactivation remarkably increased the recovery levels and stimulated the functional activity of Vδ1 + T‐cells. Whereas disability of Vδ1 + T‐cells was observed upon refractory CMV reactivation indicating the differential responses of Vδ1 + T‐cells under different CMV reactivation status. CXCL10 and IFN‐β that were dramatically induced by occasional CMV reactivation could re‐activate the deficient Vδ1 + T‐cells from recipients with refractory CMV reactivation. These findings unveiled the distinct activities of Vδ1 + T‐cells in anti‐CMV immunity after alloHCT and may help develop novel strategies for the treatment of CMV infectious diseases. Abstract : In the context of clinical alloHCT, functional activities of Vδ1 + T cells are significantly induced by occasional CMV reactivation, whereas are attenuated during refractory CMV reactivation. Mechanically, both primary and ex‐vivo expanded Vδ1 + T cells independently recognize CMV particles and CMV‐infected cells via the functional receptors (e.g. γδTCR, NKG2D and TLR2). Treatment with IFN‐β and CXCL10 can reactivate primary Vδ1 + T cells that are deficient in alloHCT recipients upon refractory CMV reactivation and enhance the anti‐CMV cytotoxicity of ex‐vivo expanded Vδ1 + T cells.